1987
DOI: 10.1128/mcb.7.4.1409
|View full text |Cite
|
Sign up to set email alerts
|

Gene recombination in X-ray-sensitive hamster cells.

Abstract: Recombination was measured in Chinese hamster ovary (CHO-Kl) cells and in the X-ray-sensitive mutants xrsl and xrs7, which show a defect in DNA double-strand break repair. To assay recombination, pairs of derivatives of the plasmid pSV2gpt were constructed with nonoverlapping deletions in the gpt gene region and cotransferred into the dilTerent cell types. Recombination efficiencies, measured as the transformation frequency with a pair of deletion plasmids relative to that with the complete pSV2gpt plasmid, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 45 publications
3
14
1
Order By: Relevance
“…At low DNA concentrations, little or no difference is observed between wild-type and mutant cell lines. At high DNA concentrations, as many as 5-to 10-fold fewer random integrants are obtained from xrs-6 cells and other members of the IR complementation group 5, as measured by selectable drug marker expression (27,28). These results, combined with the proficiency of these cells to undergo DSB-promoted recombination events, suggest that Ku deficient cell lines may have more desirable ratios of homologous to nonhomologous integrations in gene targeting studies, at least under some transfection conditions.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…At low DNA concentrations, little or no difference is observed between wild-type and mutant cell lines. At high DNA concentrations, as many as 5-to 10-fold fewer random integrants are obtained from xrs-6 cells and other members of the IR complementation group 5, as measured by selectable drug marker expression (27,28). These results, combined with the proficiency of these cells to undergo DSB-promoted recombination events, suggest that Ku deficient cell lines may have more desirable ratios of homologous to nonhomologous integrations in gene targeting studies, at least under some transfection conditions.…”
Section: Methodsmentioning
confidence: 61%
“…In our assays, electroporatedxrs-6 cells exhibited no deficiency in the integration of the control plasmid pMClneo, suggesting that there may be mechanistic differences between chromosome end-joining and random plasmid integration. Previous studies in xrs cells using calcium phosphate transfection have reported a defect in plasmid integration that is dependent on the concentration of the transfected DNA (27,28). At low DNA concentrations, little or no difference is observed between wild-type and mutant cell lines.…”
Section: Methodsmentioning
confidence: 94%
“…Observations on plasmid integration in Ku80p-deficient cells also implicate an additional mechanism for random integration that becomes saturated at high DNA concentrations (128,129). At low DNA concentrations little difference is observed between wild-type and Ku80p-deficient cells; however, at high DNA concentrations random integration is 5-to 10-fold lower in Ku80p-deficient cells (128,129).…”
Section: Nhejmentioning
confidence: 89%
“…Each plasmid carries a copy of the bacterial xgprt gene, which has been inactivated either by a 5Ј or 3Ј deletion (p⌬2-puro or p⌬3, respectively). Neither of the xgprt mutations are revertible, and only HR, via either gene conversion or gene crossover between these two mutant copies can reconstitute a functional xgprt gene, thereby conferring resistance to XHATM drug selection in cell culture (14,33). For cells without wt BRCA2, a mean homology-mediated chromosomal-targeting frequency of Fig.…”
Section: Brca2 Status Of Capan-1 Cellsmentioning
confidence: 99%